Data Deduplication: An approach for avoidance of duplicate data - M.Purushothaman , S.Anbarasan, G.Karthika, M.P.Ruby , S.Vijalakshmi (International Journal of Scientific Research and Management (IJSRM), 2015)
Cloud computing is an emerging technology; it provides many services regarding software, infrastructure, storage, etc. Storage as a service is very eminent service and makes users to use their storage space resourcefully. In cloud computing, to reduce the utilization of storage area and bandwidth data deduplication technique is used. This technique eliminates the redundancy data. To provide semantic security for the data, a new scheme is projected. By sorting out the data as encrypted and un-encrypted data can attain semantic security than existing system. To improve the rate, reliability and accessibility of the data backup scheduling is proposed